Analysis of the effect of low dye concentration for electrical system applications of reactive red 45 dye loaded hydrogels - Ozturk, M.; Coskun, R.; Okutan, M.; Yalcin, O.; Kirsoy, A. (ELSEVIER, 2022)
Structural, optical and dielectric properties determining the conduction mechanism were investigated using appropriate measurement techniques to determine the suitability of low-concentrations (LC) (1000 mu L, 500 mu L, 250 mu L and 125 mu L) reactive red 45 (RR-45) dye loaded hydrogels for electrical circuit applications. The UV spectra of the all samples displayed a fluctuating behaviour depending on the concentration. It was found that the dielectric plane plots for all the samples are compatible with the Cole-Cole relaxation model and correspond to an equivalent electrical circuit (RC) representing with the impedance circuit in the Smith Chart. It was concluded that RR-45 dye loaded hydrogels could be a suitable material for electrodes used in electroenceph-alography and electrocardiography systems due to the decrease of the real part of complex dielectric constant and impedance values with increasing frequency. The s-parameter for the samples, which determines the con-ductivity mechanism, was calculated separately for different regions.
Keywords: Reactive red 45 dye; Dielectric properties; UV spectra; Cole-cole plots; Impedance circuit; Smith chart; DIELECTRIC-PROPERTIES; SYNTHETIC CIRCUITS; GOLD NANOPARTICLES; OPTICAL-PROPERTIES; RHODAMINE-B; CONDUCTIVITY; ABSORPTION; DISPERSION; CONSTANT; MODULUS; Physics